BIOSYNTHESIS OF COLLAGEN : Biochemical and Physicochemical Characterization of Collagen-Synthesizing Polyribosomes - Fernández-Madrid, F. (The Rockefeller University Press, 1967)
Synthesis of collagen on polyribosomes has been demonstrated in vitro in chick embryo corium by radioisotope incorporation, zone centrifugation through sucrose gradients, and analytical ultracentrifugation. Collagen synthesis was associated with polyribosomes ranging in size, as reflected by their sedimentation constants, from about 180S to approximately 1600S. Most of the newly formed collagen, hydroxyproline, was present on the largest polyribosome aggregates (∼ 350–1600S), but small polyribosomes (∼180–200S) also contained collagen. On the basis of the proline-(14)C/hydroxyproline-(14)C ratios and the disrupting effect of collagenase, the proposal is made that the 350–1600S polyribosomes from this tissue are involved predominantly in collagen synthesis. The large polyribosomes are disrupted extensively by collagenase but only partially by ribonuclease and trypsin. Therefore, it appears that they are stabilized by the interaction of newly forming collagen chains. Evidence is presented consistent with the hypothesis that these large polyribosomes are formed by the aggregation of small polyribosomes (180–200S) through the interaction of collagen polypeptides. It is suggested that these small polyribosomes might be involved in the synthesis of subunits of the collagen alpha chain.